Population biology and ecology of the critically endangered succulent adenium swazicum - Van der Walt, Karin (My University, 2016)
Adenium swazicum is currently listed as Critically Endangered due to past and future population declines, which have been estimated to be 80% over three generations. Although 10-20% of the population is present in formal protected areas, no studies have been published on the species population biology and ecology, which are essential to ensure its effective conservation. The broad aim of this research was to investigate the population biology and ecology of Adenium swazicum by investigating factors such as current distribution, population structure, reproductive characteristics, germination, herbivory and current threats. The current distribution of Adenium swazicum was determined by searching all herbarium records on the National Herbarium Pretoria Computerised Information System as well as additional suitable habitat through fieldwork, conducted during the flowering period (October to April) between 2009 and 2011. The current Extent of Occurrence (EOO) and Area of Occupancy (AOO) were determined by incorporating all confirmed localities of Adenium swazicum. To determine the population biology of Adenium swazicum, fifty plants in four representative populations were studied with regards to plant size, extent and intensity of herbivory, flower production as well as follicle and seed production. The reproduction of Adenium swazicum was determined through pollinator observations while the number of flowers and fruit (follicles) produced, as well as fruit and seed set were compared in the four representative populations. Seed viability was determined through tetrazolium staining, while germination experiments were used to determine minimum, maximum and optimum temperature ranges as well as mean germination time. Seedling emergence and establishment were determined for various soil media, depth of seed planting, watering regimes and shading. The current distribution of A. swazicum included 23 localities in South Africa, Swaziland and Mozambique, while the Extent of Occurrence (EOO) was approximately 8 392km² (839 246 ha) and the Area of Occupancy (AOO) was estimated to be 8.5km² (850ha). Although this indicates that A. swazicum might be more widespread than previously believed, the population sizes were all small (between 1 and 141) and most of the populations were still threatened, mostly by habitat destruction and harvesting for medicinal purposes. The research found that adult A. swazicum plants were found to have a high tolerance to natural disturbance (fire, herbivory) and resprout from the underground tuber even if all above ground parts were destroyed. It is however unlikely that seedlings and juveniles will be able to withstand significant impact on the above ground parts since the underground tuber only develops in plants older than 24 months. Despite big and bright floral displays which should attract insect pollinators, low diurnal insect activity was observed around A. swazicum. However, a fast flying Sphingidae (Hawk Moth), which is most likely a pollinator, was observed at A. swazicum flowers at dusk. Small population size and isolation might have been the cause of no reproduction (very few follicles and no seed) in at least one population in 2010. Continued reproduction failure as well as destruction of remaining adult plants by housing developments and collection for medicinal purposes might lead to the local extinction of this population. With sufficient available moisture, high germination success (82 to 90%) for A. swazicum was achieved at temperatures between 20°C and 35°C, without any pre-treatment, and ‘maximum’ germination was reached in less than 90 hours. The cultivation of A. swazicum from seed is highly successful, with different soil media having no apparent influence on seedling emergence and establishment. Seedling emergence was highly dependent on water, and although shading did not influence seedling emergence, seedling establishment/survival was highly dependent on shading. Since seed release from A. swazicum coincides with the start of the rainy season (October), as well as short germination responses, it is highly unlikely that A. swazicum forms persistent soil seed banks. The uncomplicated propagation of A. swazicum has resulted in a significant ex situ collection at the Lowveld National Botanical Garden, with more than 2000 plants (adults and seedlings) grown from seeds which were collected from four different populations over an eight year period. In addition, the Skukuza indigenous nursery in Kruger National Park has more than 250 plants (adults and seedlings) all of which were grown from seed collected in the KNP. These living ex situ collections provide a valuable source of plant material for future restoration projects. Despite an increase in the number of known Adenium swazicum populations, the population sizes are small (1 to 141) and most populations are still threatened by habitat destruction and high levels of exploitation by medicinal plant harvesters. It is therefore recommended that Adenium swazicum remains listed as Critically Endangered (A4acd;B2cb). Criteria A4acd: “An observed, estimated, inferred, projected or suspected population reduction (up to a maximum of 100 years) where the time period must include both the past and future, and where the causes of reduction may not have ceased or, may not be understood, or may not be reversible based on”. This assessment was based on (a) the causes of reduction of Adenium swazicum populations have not ceased and may not be reversible, (c) there is a decline in AOO, EOO and habitat quality; and (d) there is actual, continuing exploitation of A. swazicum. Adenium swazicum also qualifies as CR under criteria B2b(iv,v): “Geographic range in the form of Area of Occupancy (AOO) of <10km² with (b) continuing decline in (iv) number of locations or subpopulations and (v) number of mature individuals”. No immediate management intervention is needed for populations which are located in formal protected areas, although it is recommended that these populations be monitored, especially with regards to reproduction to inform future management decisions. It is possible that low seed viability recorded in population C in 2009 and 2010 could be due to inbreeding depression caused by the destruction of surrounding populations due to sugarcane fields and harvesting of adult plants for medicinal uses. The Low veld National Botanical Garden had collected parental material from populations surrounding population C since 2003; it is recommended that restoration of decimated populations be conducted in secure areas on for example private land and community schools. Lastly, seed collected from various populations should be banked at the Kew Millennium Seed Bank Project, England to ensure viable ex situ collections.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science June 2015
Keywords: Population biology.; Succulent plants.; Cactus--Ecology.